2003
DOI: 10.2117/psysoc.2003.38
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Self-Regulation: Processes Involved and Context Effects-a Discussion

Abstract: and Hirotsugu YAMAUCHI 3)3) Doshisha University, JapanAs the title of this special issue denotes, there are two concepts that are being brought together: motivation and self-regulation. The special issue, however, is focusing on the relations of these concepts in the case of learning rather than in other situations. The learning situation is theoretically significant because learning pervades all human activity and demands effort and persistence over long period of time. It also requires selfdetermination, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Metacognitive skills/strategies consist of orientation, planning, cognitive processing, monitoring, and evaluation approaches (Veenman & Elshout, 1999). Efklides et al (2003) argued that metacognitive skills are not analogous to self-regulation. However, Pintrich et al (2000) suggested that metacognitive skills constitute part of the self-regulation process.…”
Section: Introductionmentioning
confidence: 99%
“…Metacognitive skills/strategies consist of orientation, planning, cognitive processing, monitoring, and evaluation approaches (Veenman & Elshout, 1999). Efklides et al (2003) argued that metacognitive skills are not analogous to self-regulation. However, Pintrich et al (2000) suggested that metacognitive skills constitute part of the self-regulation process.…”
Section: Introductionmentioning
confidence: 99%